Stereotactic Body Radiotherapy vs. Radiofrequency Ablation in the Treatment of Hepatocellular Carcinoma: A Meta-Analysis - Pan, Yang-Xun; Fu, Yi-Zhen; Hu, Dan-Dan; Long, Qian; Wang, Jun-Cheng; Xi, Mian; Liu, Shi-Liang; Xu, Li; Liu, Meng-Zhong; Chen, Min-Shan; Zhang, Yao-Jun (Frontiers in Oncology, 2020)
Background: Both stereotactic body radiotherapy (SBRT) and radiofrequency ablation (RFA) are effective local treatments for hepatocellular carcinoma (HCC), but whether RFA is superior to SBRT is still controversial. Therefore, we performed a meta-analysis to compare the treatment outcomes of SBRT with RFA as curable or bridge intention. Methods: We searched online databases for studies that compared treatment outcomes for SBRT and RFA. Eligibility criteria included evaluation of local control, overall survival (OS), transplant rate, and post-transplant pathological necrosis. Results: As no randomized clinical trials met the criteria, 10 retrospective studies with a total of 2732 patients were included. 2 studies were in favor of SBRT in local control, 2 studies preferred RFA in OS and others reported comparable outcomes for both. SBRT demonstrated significantly higher 1- and 3-year local control than RFA (OR 0.42, 95% CI 0.24 to 0.74, P=0.003; OR 0.54, 95% CI 0.37 to 0.80, P=0.002, respectively). However, SBRT reported significantly shorter 1- and 2-year OS (OR 1.52, 95% CI 1.21 to 1.90, P=0.0003; OR 1.66, 95% CI 1.38 to 2.01, P<0.00001, respectively). As bridge treatment, no significant difference was shown in transplant rate and post-transplant pathological necrosis rate (OR 0.57, 95% CI 0.32 to 1.03, P=0.060; OR 0.49, 95% CI 0.13 to 1.82, P=0.290, respectively). Conclusions: This study demonstrates SBRT is able to complete a better local control for HCC than RFA, though the OS is inferior to RFA because of tumor burden or liver profiles of the enrolled studies. Well-designed, randomized, multicenter trials will be required to further investigate the conclusion.